2016
DOI: 10.1155/2016/1717352
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Organic Farming in Bhutan: A SWOT Analysis

Abstract: A study was conducted to investigate the prospects of organic agriculture (OA) in Bhutan from the experts' perspective, particularly the SWOT (strength, weakness, opportunity, and threat) aspect. Thirty-five Bhutanese experts were interviewed. The strengths of OA were (i) good alignment of the principles of OA with Bhutan's development philosophy, (ii) strong policy and political support, (iii) pristine environment, (iv) OA practices similar to traditional farming, and (v) compatibility of OA with the local fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…Livelihoods are dependent on natural resources in the South Asia and are therefore climate sensitive. A study in Bhutan showed that some of the threats to organic farming originated from a change in climate, reduction in sources of organic manure and decrease in yield (Tashi and Wangchuk, 2016). Sea-level rise, rise in flooding, thermal and water stress are anticipated to affect agriculture and aquaculture.…”
Section: Impact Of Climate Change On Livelihood Of Womenmentioning
confidence: 99%
“…Livelihoods are dependent on natural resources in the South Asia and are therefore climate sensitive. A study in Bhutan showed that some of the threats to organic farming originated from a change in climate, reduction in sources of organic manure and decrease in yield (Tashi and Wangchuk, 2016). Sea-level rise, rise in flooding, thermal and water stress are anticipated to affect agriculture and aquaculture.…”
Section: Impact Of Climate Change On Livelihood Of Womenmentioning
confidence: 99%
“…Threats: Threats is also an external factors for what a industry should definetly worry about. Because this factor cannot be regulated and it is the main reason for market fall (Tashi & Wangchuk 2016) [17] .…”
Section: Strengthsmentioning
confidence: 99%
“…The indiscriminate overgrazing practice has caused an open conflict between Radips and Brokpas that has prevailed over 3 decades. Cattle of opposing communities have been injured and killed (Tashi and Wangchuk 2006), and the conflict has led to several court cases (Tenzing et al 2017b).…”
Section: Collaborative Modeling and Simulation To Mitigate High-eleva...mentioning
confidence: 99%